Growth of plasma-enhanced chemical vapour deposition and hot filament plasma-enhanced chemical vapour deposition transfer-free graphene using a nickel catalyst - Othman, Maisara; Ritikos, Richard; Rahman, Saadah Abdul (Elsevier, 2019)
This paper investigates the effects of radiant heat from implementing a hot filament (HF) in an existing Plasma-enhanced Chemical Vapour Deposition (PECVD) system on the growth of transfer-free graphene. The fabrication and properties of the transfer-free graphene grown using the HF-PECVD technique with nickel (Ni) as a catalyst were compared to that of transfer-free graphene grown using the existing PECVD method. The Ni film was used as a catalyst to assist the formation of graphene at the Ni-substrate interface for both techniques. Instead of undergoing an additional Ni annealing process, an increase in deposition temperature was achieved from the radiant heat of the hot filament in the HF-PECVD, changing the Ni grain size from nano-sized to micro-sized and reducing the formation of Ni grain boundaries. The increase in Ni grain size and the reduction in the grain boundary formation promoted the formation of less defective graphene with a more ordered structure. The formation of well-ordered graphitic-structured graphene also corresponded to the disappearance of O contamination in the Ni catalyst due to the higher deposition temperature. The enhancement in the structure, morphology, and chemical bonding of the transfer-free graphene grown using the HF-PECVD technique resulted in improved electrical properties of the film. © 2019 Elsevier B.V.